2021
DOI: 10.1016/j.heliyon.2021.e08053
|View full text |Cite
|
Sign up to set email alerts
|

Professional development among English language teachers: challenges and recommendations for practice

Abstract: Professional development of language teachers is one major measure to ensure that teachers remain updated and avoid the risk or leaving the profession. Not all teachers, however, attend professional development (PD) workshops or engage in such activities for the sake of developing professionally. Some teachers attend PD courses on a routine basis with little knowledge of what competencies they are expected to gain as a result, and simply because taking part in such programmes is an institutional requirement. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 10 publications
2
19
0
Order By: Relevance
“…This finding concurs with Peeples, Hirsch, Gardner, Keeley, Sherrow, McKenzie, and Kennedy (2019), who highlighted the effectiveness of multimedia training in facilitating learning and acquisition. Hands-on online lesson planning, practical delivery sessions, and peer feedback further contributed to the training participants' learning, acquisition, and transfer of PD content, as triangulated with Sadeghi and Richards (2021). They stated that when teachers are engaged in the planning and implementing PD training content in their classrooms, they gain ownership of the learning, which facilitates the acquisition of content knowledge.…”
Section: Just-in-time Accessmentioning
confidence: 95%
“…This finding concurs with Peeples, Hirsch, Gardner, Keeley, Sherrow, McKenzie, and Kennedy (2019), who highlighted the effectiveness of multimedia training in facilitating learning and acquisition. Hands-on online lesson planning, practical delivery sessions, and peer feedback further contributed to the training participants' learning, acquisition, and transfer of PD content, as triangulated with Sadeghi and Richards (2021). They stated that when teachers are engaged in the planning and implementing PD training content in their classrooms, they gain ownership of the learning, which facilitates the acquisition of content knowledge.…”
Section: Just-in-time Accessmentioning
confidence: 95%
“…Furthermore, this study also found that the principal encouraged the teachers to actively participate in the Teacher Work Group (MGMP) as a forum for teachers to exchange ideas with their professional colleagues. This is supported by a study by Sadeghi & Richards (2021) on developing the professional abilities of English teachers in Iran which includes ministry of education (public) teachers, language center (private) teachers, and all teachers working in the public and private sector. The study suggested that teachers are allowed to be able to join the discussion group of their professional colleagues.…”
Section: Figure 14 Learning Teacher Programmentioning
confidence: 99%
“…Therefore, she felt pressured when she knew her colleagues could teach with technology because she needed more confidence with her DLC (Table 6). Hence, P2's responses unveil the suggestion that peer discussion (between colleagues) after teaching practices in an EFL classroom can be a medium to increase the lecturers' professionalism (Sadeghi & Richards, 2021).…”
Section: The Correlations Of the Efl Lecturers' Dlc And Technostress ...mentioning
confidence: 99%